Junio León, new bean variety for irrigation and rainfed for the Highlands and Central Mexico - Acosta-Gallegos, Jorge Alberto; Jiménez-Hernández Yanet; Montero-Tavera Víctor; Sánchez García Bertha María; Guzmán-Maldonado Salvador Horacio (Revista Mexicana de Ciencias Agrícolas, 2018)
Beans of Junio Flower type is in high demand in the center of Mexico region, produced under irrigation and rainfed conditions in the States of Zacatecas, San Luis Potosí and Guanajuato, mainly. The new variety Junio León was derived from the single cross Junio Flower Marcela by Flor de Mayo Anita conducted in 2004 in the Experimental Field El Bajío. Is indefinite-prostrate habit and adapts well to planting in double rows or single row. The grain size is medium (34 g in 100 grains), cream and pink striped background. It is resistant to common blight and halo blight and temporary low has a lower incidence (1.8) rust, compared to Junio Flower Marcela (4). Junio León has markers associated with Ur6 and Ur 9 genes of Andean origin, because important genes in combination with genes having Mesoamerican origin (Ur 3 Ur 4 Ur 5 GB), show a wide spectrum of rust resistance. In protein content, grain Junio León was higher than Marcela under irrigation and similar under rainfed, also cooking time was similar under both conditions.